Ethical Entrepreneurial Leadership And Its Impact On Entrepreneurial Orientation Through The Mediating Role Of Entrepreneurial Passion: An Analytical Study Of The Opinions Of A Sample Of Owners Of Sme In Diwaniyah Governorate - Basim Abbas Kraidy Jassmy (International Forum of Researchers and Lecturers, 2024)
The current study aims to identify the impact of ethical entrepreneurial leadership on theentrepreneurial orientation of SME owners in the Diwaniyah Governorate. According to the above, thestudy adopts a descriptive and analytical approach to its variables. The study sample consisted of agroup of SME ownwers , numbering (70) companies out of (90). The questionnaire forms was used asa essential tool for collecting data. The study were used many statistical methods such as standarddeviations, arithmetic mean , and structural equation modeling with the help of statistical programs(SPSS.var.24, Smart PLS). Theis exist study reached a set of useful conclusions and recommendations.Basically important of which is that the results of the statistical analysis showed that ethicalentrepreneurial leadership has a significant impact on entrepreneurial orientation.